MBCL-48. HEARING CHEMOPROTECTION WITH SODIUM THIOSULFATE (STS) IN CHILDREN, ADOLESCENTS AND YOUNG ADULTS WITH STANDARD RISK MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Neuwelt, Edward; Lindemulder, Susan; Knight, Kristin; Fu, Rochelle; Bleyer, Archie; Brock, Penelope
Abstract: Platinum based chemotherapies are essential for treating certain pediatric cancers, but cause significant ototoxicity in many patients. While patients with localized medulloblastoma have an overall survival of more than 80%, many survivors develop hearing loss requiring lifelong use of hearing aids and have markedly decreased long term quality of life. In a series of 41 pediatric patients at OHSU treated for standard risk medulloblastoma, 7 (17%) developed ototoxicity after the second cisplatin cycle and 26 (63%) had hearing loss following the fourth cycle. Cisplatin dose reductions were required for 24 (59%) patients due to hearing loss. At the end of treatment 32/38 (84%) had hearing loss and 12 required hearing aids. Two randomized phase III trials, one conducted by the Children's Oncology Group (COG ACCL0431) and the other by the Société Internationale d'Oncologie Pédiatrique - Epithelial Liver Tumor Study Group (SIOPEL 6), have demonstrated the efficacy of sodium thiosulfate (STS) in protecting children from cisplatin-induced hearing loss. Both studies showed no impact of STS on progression-free or overall survival in patients with localized disease (Freyer, 2017; Brock, 2017). In the COG study medulloblastoma subgroup, hearing loss was seen in 33% (3/9) of those treated with STS vs 100% (10/10) in the observation arm. We conclude that STS may safely and effectively protect against hearing loss in medulloblastoma patients with localized disease.